PENGGUNAAN INTERPOLASI HERMITE KUBIK DALAM PENYELESAIAN PERSAMAAN STURM-LIOUVILLE DENGAN METODE ELEMEN HINGGA - Maryono, Dwi (Journal of Mathematics and Mathematics Education, 2011)
ABSTRACT: Eigenvalue problems especially Sturm-Liouville equations often occur in physics. Homogenous Dirichlet or mixed boundary value problems can be constructed from these equations. The nontrivial solution from these equations can be obtainedÂ  using finite element methods. The purpose of this research is to obtain the details ofÂ  theÂ  constructionÂ  ofÂ  finiteÂ  elementÂ  methodÂ  usingÂ  cubicÂ  HermiteÂ  interpolationÂ  inÂ Â Â  solvingÂ  Sturm-Liouville equations. The result shows that the solutions of the finite element method using cubic Hermite interpolation isÂ  goodÂ  enoughÂ  inÂ  solvingÂ  SturmÂ  LiouvilleÂ  equation.Â  BasedÂ  onÂ  theÂ  example,Â  itsÂ  errorÂ  dependsÂ  onÂ  the elementâs length and the index of the eigenvalue or eigen function. Keywords : finite element, Sturm-Liouville, Hermite Interpolation, Eigen value